Physical Education Learning Motivation: A Gender Analysis - Lutfi Nur; Adang Suherman; Herman Subarjah; Dian Budiana (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2019)
The purpose of this study was to find out the motivation of learning physical education based on gender. This study used a descriptive comparative method. The subjects in this study were 50 students in VII grade consisting of 30 male students and 22 female students. The instrument used by researchers was a physical education learning motivation questionnaire for junior high school students developed by Nur, Suherman, and Subarjah that contains 29 approved items with a validity value 0.518 and reliability value 0.906. The data analysis used an independent sample t test to analyze the motivation differences between male students and female students. The results of the study showed that the male students' physical education learning motivation was higher than female students in junior high school level. This finding is expected to be an assessment of the relevant parties in order to foster motivation to improve student learning outcomes. AbstrakTujuan penelitian ini adalah untuk melihat motivasi belajar pendidikan jasmani berdasarkan jenis kelamin. Penelitian ini menggunakan metode deskriptif komparatif. Subyek dalam penelitian ini adalah siswa SMP kelas VII dengan jumlah 52 orang siswa, terdiri dari 30 siswa laki-laki dan 22 siswa perempuan. Instrumen yang digunakan oleh peneliti adalah angket motivasi belajar pendidikan jasmani untuk siswa SMP yang terdiri dari 29 item pernyataan dengan nilai validitas 0,518 dan reliabilitas 0,906. Analisis data yang digunakan adalah independent sample t test untuk menguji perbandingan motivasi siswa laki-laki dengan siswa perempuan. Hasil penelitian menunjukkan bahwa motivasi belajar pendidikan jasmani siswa laki-laki lebih tinggi dibandingkan siswa perempuan di jenjang SMP. Adanya temuan ini diharapkan menjadi evaluasi bagi pihak-pihak terkait dalam rangka menumbuhkan motivasi guna peningkatan hasil belajar siswa.